2011
DOI: 10.1097/bot.0b013e31821c0a2f
|View full text |Cite
|
Sign up to set email alerts
|

Modern Perspectives of Open Reduction and Plate Fixation of Proximal Humerus Fractures

Abstract: Recent innovations have greatly increased the range of proximal humeral fractures that are amenable to open reduction and plate fixation.The optimum technique for some of the more complex fracture patterns is not yet fully refined.This article aims to describe the recent advances in the treatment of complex proximal humeral fractures by open reduction and locking plate fixation, focusing particularly on the indications for surgery, the operative techniques, and the expected outcomes after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 151 publications
0
42
0
4
Order By: Relevance
“…[12,15,16] Proksimal humerus kırıklarının osteosentezinde karşılaşılan komplikasyonların içinde en çok erken revizyon gerektireni eklem içi vida penetrasyonudur. [2,6,8,11,[17][18][19] Herhangi bir nedenle yapı-lan tekrar ameliyat proksimal humerus kırıklarının büyük çoğunluğunu oluşturan yaşlı hasta nüfusunda ciddi morbiditelere neden olmaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[12,15,16] Proksimal humerus kırıklarının osteosentezinde karşılaşılan komplikasyonların içinde en çok erken revizyon gerektireni eklem içi vida penetrasyonudur. [2,6,8,11,[17][18][19] Herhangi bir nedenle yapı-lan tekrar ameliyat proksimal humerus kırıklarının büyük çoğunluğunu oluşturan yaşlı hasta nüfusunda ciddi morbiditelere neden olmaktadır.…”
Section: Discussionunclassified
“…Osteosentezin ideal ve stabil olması için humerus başı-na en az beş adet vida gönderilmesi ve bunların herbirinin subkondral kemiğe 5-10 mm kalacak kadar ilerletilmesi önerilmektedir. [2,8,10,15] Vidaların olması gerekenden kısa olarak uygulanması ise özellikle osteoporotik kemikte implantın rijiditesinden dolayı yetmezlik ile sonuçlanacaktır. Bu amaçla ameliyat esnasında daha çok kemik yakalamak için mümkün olduğunca uzun vida kullanılmaya çalışılması primer vida penetrasyonunun en önemli nedenidir.…”
Section: Discussionunclassified
“…경피적 핀고정술, 관혈적 정복 및 금속판 고정술, 골수강내 고정술과 같은 다양한 수술적 치료가 행해지고 있으나 나사못의 관절면 침투, 금 속물의 이완, 금속판의 파손과 불유합과 같은 수술 후의 합병증도 30%까지 보고되고 있다 6,9,16,19) . 이는 악화된 견관 절의 기능을 가져올 뿐 아니라 최고 40%까지의 추가적인 수술적 치료를 필요로 하므로 수술적 치료의 큰 단점이 되 며, 특히 골다공증이 동반된 경우 위의 합병증의 가능성은 높아진다 4,[13][14][15]18,19) . 보존적 치료는 수술적 치료가 어려운 내과적 질환이 있는 환자에서 적응증이 될 수 있다는 보고 가 있지만 11) , …”
Section: 서 론unclassified
“…Osteoporosis often limits the success of devices to gain fixation in the proximal fragment in this region. Although there are a myriad of fixation devices available, recent studies have demonstrated good results with locking plates [1,7,9,14], locking rods [17], various percutaneous pin techniques [10,12], and even suture fixation [6]. The variety of hardware options and techniques suggests there is no single best approach for many proximal humerus fractures, and that we still have much to learn about how to manage patients with these injuries.…”
mentioning
confidence: 99%